Resident characteristics to evaluate during recruitment and interview: a Delphi study. Issue 2 (4th March 2017) - Martin, Matthew; Salzberg, Lenard
Abstract: Background and objectives : The recruitment and interview process for medical residency programmes is a time- and resource-intensive effort. There is very little research to guide programmes when evaluating residency candidates. This study represents one step in identifying candidate characteristics to assess during the recruitment and interview process. Methods : Sixteen expert interviewers from 14 family medicine residency programmes in North Carolina participated in a three-round Delphi study to build consensus around a ranked list of successful resident candidate characteristics. An interrater reliability analysis produced average pair-wise agreement and Krippendorff's Alpha coefficients. Results : Clinical skills, medical knowledge, interpersonal and communication skills, critical thinking, and professional and ethical behaviour were the highest ranked characteristics. Average pair-wise agreement for rounds two and three were 6.30 and 11.04%, respectively. Conclusions : Residency programmes may benefit from using an empirically studied list of characteristics to evaluate candidate applications and interviews. Future research should include national surveys of expert interviewers from a variety of residency programmes and a longitudinal study to correlate interview evaluations using the ranked list with measures of residency success.